Physiological Changes of Beer Brewer's Yeast During Serial Beer Fermentation. (2nd January 2019) - Wang, Jinjing; Ding, Huajian; Zheng, Feiyun; Li, Yongxian; Liu, Chunfeng; Niu, Chengtuo; Li, Qi
Abstract: Serial repitching of beer brewer's yeast plays an important role in the beer industry as an ineluctable economic factor. In this study, the viability and vitality changes, as well as strains' anti-autolytic abilities during serial beer fermentation with typical ale and lager yeast strains, were investigated. While measuring the survival rate of yeast cells is not sufficient for evaluating and predicting the yeast fermentation capacity, physiological status determination of brewer's yeast reflects the vitality and quality of yeast in serial beer fermentations. Accumulation of reactive oxygen species in yeast causes cell damage, leading to a decline in cell vitality and viability. Aged yeast cells, after several repitchings, can result in leakage of intracellular compounds into the fermented liquor. The lager yeast (Pilsner) examined, which harbors the partial genome from S. eubayanus, showed better robustness and higher activity than the ale yeast strain M79 examined, during serial fermentation. A holistic approach, including more indicators, should be applied in evaluating the fermentation performance of brewer's yeast.